La cuestión hombre tecnología: Dasein en las redes de las nuevas tecnologías (2007)
The purpose of this article is to show "man" in the networks of new technologies, in a philosophicalsense; where "man" also covers the being, his being not only from an anthropological perspective. Atthe present time a new world conception is required under the technological networks. Likewise, thisman-in-the-world disclosure takes us to other ethical, political and cultural matters. Here we willresort to the German thinker Martin Heidegger, since his proposal can contribute to the explanation ofman-technology at the present time; in as much as, he asks himself for the essence of technique departing to téchne and he also offers two new concepts to approach the being-in-this-world of thenew technologies: the Gestell and the Kehre.